Reading comprehension in Spanish language and literature manuals of the second cycle of Elementary Education - Beatriz Sánchez Hita (Investigaciones Sobre Lectura)
This paper deals with the readings and reading comprehension exercises from a representative set of Spanish language and Spanish literature textbooks, used in the second cycle of Elementary Education in Andalusia. Specifically, we attend on the typology of the texts, the selected authors and books and the exercises focused on the readings. The objective of the study is the determination of how the proposed texts help in the reading comprehension and which are the better ways to work with them.